Thermodynamic analysis of the difference in adsorption characteristics of CH4 and CO2 on continental shale - Xue, Pei; Liang, Quansheng; Gao, Chao; Yin, Jintao; Hao, Shiyan; Zhao, Qianping (Frontiers in Earth Science, 2023)
In order to explain the difference in adsorption characteristics of CH4 and CO2 on continental shale from the perspective of thermodynamics, the isothermal adsorption experiments of CH4 and CO2 adsorbed by shale in Yanchang Formation in Ordos Basin were carried out, and the excess adsorption capacity was corrected to absolute adsorption capacity. Then the Clausius-Clapeyron equation was used to analyze the isosteric heat of adsorption of CH4 and CO2 on shale. The results show that, for calculating the absolute adsorption capacity, Ozawa empirical formula or Van der Waals approximation method should be used to calculate the adsorption phase density. The absolute adsorption capacity should be selected as the basic data for calculating the isosteric heat of adsorption. The reason is that the excess isosteric heat of adsorption has a negative value in the low adsorption capacity stage, which is contradictory to the fact that the adsorption process is exothermic, and is significantly higher than the absolute isosteric heat of adsorption. There is a good linear positive correlation between the isosteric heat of adsorption and the adsorption amount of CH4 and CO2 adsorbed by continental shale, and the isosteric heat of adsorption of CH4 is greater than that of CO2. The absolute initial isosteric heat of adsorption of CH4 and CO2 adsorbed by shale is 52.04 kJ / mol and 27.71 kJ / mol, indicating that the adsorption force of CH4 on Yanchang Formation shale is stronger than that of CO2.